Emergency surgery for colon carcinoma in the elderly: audit of a 13-yr experience - Tatulli, Francesco; Caputi, Antonio; Caraglia, et al., Angelo (European Journal of Oncology and Environmental Health, 2014)
Aim: The incidence of colon carcinoma progressively increases with age. The initial presentation may be  a surgical emergency associated with increased morbidity and mortality in up to 15% of cases. The aim of this study was to perform a retrospective audit of our experience with emergency surgery for colon carcinoma in the elderly in the last 13 years. Materials and methods: From January 2000 to December 2012 we performed 879 emergency operations, of which 123 addressed colon diseases (14%), 41 colon carcinoma (1/3 of colon cases, 4.6% of the total number) on an emergency basis. Patients (pt’s) were divided into 2 age groups: A ≥75 years and B ≤74. Fourteen factors were investigated: age, gender, pre-operative ASA score, clinical presentation, types of operation, associated procedures, distribution among surgeons, tumor location, TNM stage, Hinchey stage when applicable, associated pathology, post-operative length of stay, complications, mortality. Data were recorded on a Microsoft Access 2007 database. Results: Distribution among sexes was even. A prevalent ASA III score occurred in group B. Resection was mostly performed in both groups. No differences were recorded regarding location, indication, type of operation, post-operative stay. An association was noticed between age and the following items:  TNM stage, i.e. group B showed more advanced stages, complications, i.e. more complications in group A and mortality which was higher in group A. Conclusions: Age should not be an absolute indicator to decide on a possibly life-saving emergency procedure for colon carcinoma but worse outcomes may be expected in older pt’s.